ANODE COMPOSITE ELECTROCHEMICAL IMPEDANCE IMPROVEMENT WITH LIME EXTRACT SINTERING FOR LITHIUM CERAMIC BATTERY APPLICATION - Iqbal Ashari; Solly Aryza; Adi Sastra P Tarigan (Sean Institute, 2022)
Synthesis of silica Li4Ti5O12/soda lime composite has been carried out for the anode component of lithium ceramic battery. The Li4Ti5O12 synthesis method is SSR (solid state reaction) from Li2CO3 and TiO2 powders. All lithium-based materials were calcined at 700oC for 2 hours, then ball milled to obtain finer particles and passed to a filter of less than 400 mesh. Before sintering the powder is dissolved in 99% methanol to make a paste. The Li4Ti5O12 paste was sintered at various temperatures from 750oC, 800oC, 850oC, 900oC to 950oC for 2 hours to obtain optimum electrical properties. The phase formed after sintering was identified by XRD.